ANALISIS PERAN ORANG TUA DAN GURU DALAM MENINGKATKAN SOFT SKILL PUBLIC SPEAKING SISWA - Cahyani; Hamna; Hasia Marto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This qualitative phenomenological research examined the role of parents and teachers in supporting the development of public speaking soft skills of fourth grade students of SDN Malulu, Tolitoli Regency.The study found two problems: students' lack of confidence in expressing their opinions and the lack of family support in communication.The study involved five participants: one homeroom teacher, two students (male and female), and two parents. The data were collected through various means, including observation, interviews, and documentation. These data were then analyzed using a variety of methods, including data reduction, data presentation, and conclusion drawing.The results of the study indicated that parents and teachers have important and complementary roles in supporting the development of public speaking soft skills in fourth grade students. Specifically, the findings showed that parents play a crucial role in fostering students' confidence and communication skills within the home environment. In contrast, teachers have a pivotal role in developing these skills through structured learning activities in the classroom.The collaboration between parents and teachers is found to be highly effective in nurturing students who possess both confidence and proficiency in public speaking. The comprehensive analysis of interviews and observations yielded a nuanced understanding of the contributions of parental and teacher support to students' development of social and public speaking skills.The findings of this study demonstrate the efficacy of parental and teacher support in fostering students' public speaking abilities, underscoring the significance of collaborative efforts in educational settings Keywords: Public Speaking, Teacher, The Role of Parents